2020
DOI: 10.3389/fmolb.2020.577285
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms for Traditional Chinese Medicine in Treating Airway Mucus Hypersecretion Associated With Coronavirus Disease 2019

Abstract: BackgroundThe rapid development of coronavirus disease 2019 (COVID-19) pandemic has become a great threat to global health. Its mortality is associated with inflammation-related airway mucus hypersecretion and dysfunction of expectoration, and the subsequent mucus blockage of the bronchioles at critical stage is attributed to hypoxemia, complications, and even death. Traditional Chinese medicine (TCM) has rich experience in expectorant, including treatment of COVID-19 patients with airway mucus dysfunction, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…The infection causes systemic endothelial dysfunction in COVID-19, which causes hemostasis disorders accompanied by platelet adhesion and aggregation activity, resulting in death due to blood clots in COVID-19 patients (Petrishchev et al, 2020). Furthermore, spontaneous circulation disorder is partly due to a cytokine syndrome that is closely related to a decrease in lymphocyte levels which triggers a significant decrease in CD8+ T cells and is positively correlated with mortality and morbidity rates of COVID-19 patients (Guan et al, 2020;Lu et al, 2020;Debuc & Smadja, 2021). This decrease in circulation has a significant effect on the circulation of nutrient supply for tissue metabolism, which results in a reduction of the distribution of blood circulation, which results in organ damage (Noris et al, 2020;Ostergaard, 2021).…”
Section: Nursing Diagnoses For Patients With Covid-19 In the Isolation Rooms And Icusmentioning
confidence: 99%
“…The infection causes systemic endothelial dysfunction in COVID-19, which causes hemostasis disorders accompanied by platelet adhesion and aggregation activity, resulting in death due to blood clots in COVID-19 patients (Petrishchev et al, 2020). Furthermore, spontaneous circulation disorder is partly due to a cytokine syndrome that is closely related to a decrease in lymphocyte levels which triggers a significant decrease in CD8+ T cells and is positively correlated with mortality and morbidity rates of COVID-19 patients (Guan et al, 2020;Lu et al, 2020;Debuc & Smadja, 2021). This decrease in circulation has a significant effect on the circulation of nutrient supply for tissue metabolism, which results in a reduction of the distribution of blood circulation, which results in organ damage (Noris et al, 2020;Ostergaard, 2021).…”
Section: Nursing Diagnoses For Patients With Covid-19 In the Isolation Rooms And Icusmentioning
confidence: 99%
“…Therefore, modulating IL-4/IL-13/IL-17 signaling pathways may be a therapeutic strategy for SARS-CoV-2-induced mucus hypersecretion. Also, Zhang et al found that traditional Chinese medicine expectorants regulate MUC5AC expression via IL-17 and TNF signaling pathways, which are related to virus infection such as influenza virus A and human cytomegalovirus infections (95). They speculated that core herbs of the phlegm-eliminating recipe is a potential therapy in COVID-19-induced mucus hypersecretion as well.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…All this makes hypersecretion of airway mucus and mucus plugging one of the major causes of death in critically ill COVID-19 patients. A study on critically-ill COVID-19 patients assessed the levels of mucin proteins MUC1 (membrane-tethered) and MUC5AC (secreted) in the airway mucus and reported higher levels of both MUC1 and MUC5AC than healthy controls (Bikdeli et al, 2020;Carsana et al, 2020;Deshpande, 2020;Farooqi et al, 2020;Lax et al, 2020;Liu et al, 2020;Menter et al, 2020;Wang et al, 2020a;Zhang Y. et al, 2020;Lu et al, 2021).…”
Section: Immunopathologymentioning
confidence: 99%